Differences in visual attention between those who correctly and incorrectly answer physics problems - Madsen, Adrian M.; Larson, Adam M.; Loschky, Lester C.; Rebello, N. Sanjay (My University, 2012)
This study investigated how visual attention differed between those who correctly versus incorrectly answered introductory physics problems. We recorded eye movements of 24 individuals on six different conceptual physics problems where the necessary information to solve the problem was contained in a diagram. The problems also contained areas consistent with a novicelike response and areas of high perceptual salience. Participants ranged from those who had only taken one high school physics course to those who had completed a Physics Ph.D. We found that participants who answered correctly spent a higher percentage of time looking at the relevant areas of the diagram, and those who answered incorrectly spent a higher percentage of time looking in areas of the diagram consistent with a novicelike answer. Thus, when solving physics problems, top-down processing plays a key role in guiding visual selective attention either to thematically relevant areas or novicelike areas depending on the accuracy of a student’s physics knowledge. This result has implications for the use of visual cues to redirect individuals’ attention to relevant portions of the diagrams and may potentially influence the way they reason about these problems.
Keywords: Visual attention; Physics problems; Novicelike misconcpetions; Visual cues